The impact of social communication campaigns on the lives of women defenders of territorial bodies in Peru:: The case of Máxima Acuña Atalaya - Ruíz Alvarado, Inés (2023)
In the last decade, the communication campaigns of social groups fighting and resisting against the arbitrary exploitation of the commons have been carried out at the initiative of national and international non-governmental organisations that use an emblematic case as a strategy to make this social problem visible and raise awareness among citizens. The article is the result of an interdisciplinary research situated in gender studies and communications with interviews with the defender Máxima Acuña Atalaya and her family and is based on the concept of body-territory (Silva Santisteban, 2017) and ideas on eco-territorial struggles (Svampa, 2021). Through a study using the method of digital archive analysis of Máxima Acuña's participation in social communication campaigns and personal interviews, the construction of hegemonic and counter-hegemonic narratives is investigated. The study evidences a communication process in which a choral narrative is established, but as the case gains greater relevance and international attention in the mass media, the narratives that are elaborated are transformed from a collective struggle to an individual one. We also show that, as a result of these campaigns, the lives of women defenders such as Máxima Acuya, whose privacy is exposed, are affected as they are used for different purposes of delegitimisation by mining companies.